Pengaruh Prestasi Akademik dan Perbedaan Gender Terhadap Kemampuan Scientific Reasoning Mahasiswa Fisika - Adis Veliana Anjani; Yuberti Yuberti; Ardian Asyhari* (Universitas Syiah Kuala, 2022)
Scientific reasoning ability is one of the essential abilities in education for the 21st century. In addition, several studies reveal that scientific reasoning can affect academic achievement, which can also be seen from the gender aspect. The purpose of this study is to determine the effect of academic achievement on scientific reasoning abilities, the effect of gender on scientific reasoning abilities, and the relationship between academic achievement and gender differences on the scientific reasoning abilities of physics students. The participants in this study were all final-year students in the Physics Education Study Program at the State Islamic University of Raden Intan Lampung for the 2019/2020 academic year. This study's sample size was 87, with 13 males and 74 females. Purposive sampling was used in this study. The sample was selected from students nearing the end of their lecture program. The research instrument used was the Lawson classroom test for scientific reasoning, consisting of 12 multiple-reason questions with a reliability level of ,604. The study's Kruskal-Wallis test showed no significant effect between academic achievement and gender on scientific reasoning abilities. Also, the correlation test results using the spearman test showed no positive relationship between academic achievement and gender differences on the scientific reasoning ability of physics students